Тhe Tatras in the Earliest Ruthenian Translation of the Czech Book Lucidář: Localising and Chronologising the Translation - Temchin, Sergei (Senoji Lietuvos literatūra, 2020)
The article discusses the textual problems of two Ruthenian translations of the Czech book entitled Lucidář (Latin: Lucidarius), which was intended for a wide readership and became quite popular in the Middle Ages. The focus is placed on determining the chronology and localisation of the earliest Ruthenian translation known solely from the Rakošin manuscript copy of the seventeentheighteenth centuries. The author argues that the translation dates back to the mid sixteenth century, since it reflects the earlier version of the first Czech edition, which was circulating before the textual revision was made in c. 1567. The earliest Ruthenian translation can be localised according to the following textual feature of the Cyrillic text. The Mount Olympus mentioned in the Czech original is clearly identified with the Tatra Mountains in the Ruthenian translation. This place name, included in the Cyrillic version more or less incidentally, suggests that the translation was performed by a person who grew up and/or lived near the Tatras. Thus, the Ruthenian translation must have originated somewhere in the Ruthenian Orthodox areas within either the Kingdom of Hungary (nowadays in Slovakia) or the Kingdom of Poland. In any case, the Czech book Lucidář is known to have been consulted in the Polish town of Muszyna (in the southern area of the modern voivodeship of Lesser Poland) between 1911 and 1913.